Pre-Operative Embolisation of an Aberrant Pharyngeal Arterial Branch Arising From the Internal Carotid Artery and Contributing Significantly to the Supply of a Large Juvenile Nasopharyngeal Angiofibroma. (January 2022) - Dolan, Steven G.; Surda, Pavol; Sabharwal, Tarun
Preoperative embolisation of juvenile nasopharyngeal angiofibromas (JNAs) is a well-established treatment that reduces intraoperative blood loss and improves surgical outcomes. While the bulk of arterial supply to the tumour is derived from the external carotid system, some degree of contribution from the internal carotid artery (ICA) is common. ICA branch embolisation in this setting has previously been avoided due to concerns over ischaemic neurological complications, possibly contributing to the increased intraoperative blood loss observed in patients with tumours with ICA supply. There is a marked paucity of reports of embolisation of ICA branches supplying JNA in the medical literature. We present a case of successful embolisation of an aberrant pharyngeal branch of the ascending pharyngeal artery arising from the proximal cervical ICA, which was making a significant contribution to tumour blood supply in a male adolescent with a very large JNA.